Apakah APEC Memfasilitasi Perdagangan Bilateral? Bukti dari Estimasi Model Gravitasi - Marthin Thomas Mumbunan; Marianus Antonius Muga; Yoan Purnamasari Makapuase Bahalau (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Trade agreements and regional forums such as the Asia‑Pacific Economic Cooperation (APEC) and Free Trade Agreements (FTAs) are key instruments in promoting trade liberalization, though their effectiveness in enhancing bilateral trade flows remains contested. Unlike FTAs, which are legally binding and involve tariff and non‑tariff reductions, APEC is a non‑binding forum that facilitates trade through policy harmonization, cost reduction, and improved connectivity. This study evaluates the impact of APEC and FTAs on bilateral trade using the gravity model with Poisson Pseudo‑Maximum Likelihood (PPML) estimation, complemented by Pooled OLS for comparison. The results show that APEC membership has a broader and more consistent positive effect on bilateral trade than FTAs, despite the latter’s binding nature. Geographic distance remains a significant barrier, while exchange‑rate fluctuations are largely insignificant. The findings highlight that APEC’s effectiveness is shaped not only by institutional design but also by structural and domestic factors, underscoring the need for adaptive trade policies tailored to country‑specific contexts